"Assessment of the application for preventive factors of osteoporosis, in menopausal women referred to the health care centers in Tehran University of Medical Sciences " - Rasooli; F. (M.Sc); Haj Amiry; P. (M.Sc); Mahmoodi; M. (Ph.D); Abdoli; S. (M.Sc) (Tehran University of Medical Sciences, 2002)
This research is a descriptive - analytic study which has been conducted in order to assess the application for prevention of osteoporosis, on menopausal women referred to the health care centers of Tehran University of Medical Sciences in 2001. The research subjects were composed of 336 menopausal women who had been selected by two-stage sampling. The results of the research showed only 4.8% of research subject had adequate calcium intake. Also 5.1% of research subjects have been treated by hormonal drugs, 7.7% of research subjects have taken non hormonal drugs adequately, and (78/3%) had no physical activity. Also the results showed, the application of preventive agents for osteoporosis was influenced by the variables such as: age menopausal characteristic, educational level, marietal status, family income, history of bone fracture, family history of osteoporosis, having employed relatives engaged in medical group, also receiving and having preventive information.